Analisis Faktor-Faktor yang Mempengaruhi Terjadi Kredit Macet pada Koperasi Unit Desa di Kabupaten Buleleng - Saputra Komang Widiana; I Wayan Suwendra (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aims to determine the factors that affect non-performing loans in Village Unit Cooperatives in Buleleng Regency for the 2021-2024 period: (1) Debtor Business Management, (2) Worsening Operational Conditions, (3) Debtor's Good Faith, (4) Force Majeure. The population in this study were customers of the Village Unit Cooperatives in Buleleng Regency who experienced non-performing loans totaling 1,836 customers with a sample of 328 respondents. Sampling in this study was determined by the slovin formula and the Stratified Random Sampling method technique. Data were collected through questionnaires and analyzed using factor analysis with the help of Statistical Package For The Social Sciences version 23 software. The results indicate that the factors influencing non-performing loans in the Village Unit Cooperatives in Buleleng Regency include debtor business management, worsening operational conditions, debtor's good faith, and force majeure. These factors are proven to be able to form a valid and reliable construct in explaining non-performing loans. Of the 4 existing factors, the most dominant in influencing non-performing loans is debtor business management.